2013
DOI: 10.1080/03602559.2012.762662
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Poly(vinyl alcohol)/Poly(vinyl pyrrolidone)-Iodine Nanofibers with Poloxamer 188 and Chitosan

Abstract: This study focuses on the fabrication of poly(vinyl alcohol)/ poly(vinyl pyrrolidone)-Iodine nanofibers via electrospinning. Electrospun fibers were characterized by FT-IR, DSC and SEM techniques. DSC results indicated that the thermal stability of nanofibers were improved after the addition of chitosan and poloxamer 188. SEM images showed that the spongiform structure is much more compact and fibrous in the case of added chitosan, with an average fiber diameter of 374 nm, whereas the addition of poloxamer 188… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…This was due to the strong hydrogen-bonding interactions between the OH groups of PVA and the carbonyl groups in PVP; this led to an orientation of the macromolecular chain of the blend. 26 The XRD pattern of 10 wt % sericin/PVP/PVP composite showed a sharp diffraction peak at a 2h of 27.38, and we also observed that the peak at a 2h of 47.88 was absent. However, when the concentration of sericin particles was 15 wt %, the intensity of the crystalline peak at a 2h of 27.38 decreased, and the amorphous region become more prominent at a 2h of 20.68.…”
Section: Ftir Characterizationmentioning
confidence: 73%
“…This was due to the strong hydrogen-bonding interactions between the OH groups of PVA and the carbonyl groups in PVP; this led to an orientation of the macromolecular chain of the blend. 26 The XRD pattern of 10 wt % sericin/PVP/PVP composite showed a sharp diffraction peak at a 2h of 27.38, and we also observed that the peak at a 2h of 47.88 was absent. However, when the concentration of sericin particles was 15 wt %, the intensity of the crystalline peak at a 2h of 27.38 decreased, and the amorphous region become more prominent at a 2h of 20.68.…”
Section: Ftir Characterizationmentioning
confidence: 73%
“…[1][2][3][4][5][6] . Polyvinyl alcohol (PVA) hydrogels is providing a good host matrix for the embedding of metal nanoparticles [7,8] .…”
Section: Introductionmentioning
confidence: 98%
“…Variables that have been explored include polymer solubility [9][10][11], solvent polarity [2], concentration of polymer solution [3,7,12,13], and spinning parameters such as applied voltage, tip-to-collector distance (working distance), and flow rate [2,7,8]. Various results have been reported such as none of the aforementioned parameters making a difference to fiber diameter [7] to increased voltage increasing the fiber diameter and decreased voltage resulting in beading [14].…”
Section: Introductionmentioning
confidence: 99%
“…Electrospinning is the method of fiber extrusion from a needle tip on to a grounded plate via an electrostatic gradient. It differs from conventional extrusion methods since the fiber diameters that can be achieved are of submicron scale, which bestow larger surface area that allow for efficient surface functionality and high mechanical stability [1][2][3]. Nano-scale fibers yielded from electrospinning resemble that of the natural extra-cellular matrix [1,4] and are therefore of great interest for application in tissue engineering [5,6].…”
Section: Introductionmentioning
confidence: 99%